Pore‐scale investigation on stress‐dependent characteristics of granular packs and the impact of pore deformation on fluid distribution. Issue 1 (25th May 2015) - Torrealba, V. A.; Karpyn, Z. T.; Yoon, H.; Klise, K. A.; Crandall, D.
Abstract: Understanding the effect of changing stress conditions on multiphase flow in porous media is of fundamental importance for many subsurface activities including enhanced oil recovery, water drawdown from aquifers, soil confinement, and geologic carbon storage. Geomechanical properties of complex porous systems are dynamically linked to flow conditions, but their feedback relationship is often oversimplified due to the difficulty of representing pore‐scale stress deformation and multiphase flow characteristics in high fidelity. In this work, we performed pore‐scale experiments of single‐ and multiphase flow through bead packs at different confining pressure conditions to elucidate compaction‐dependent characteristics of granular packs and their impact on fluid flow. A series of drainage and imbibition cycles were conducted on a water‐wet, soda‐lime glass bead pack under varying confining stress conditions. Simultaneously, X‐ray micro‐CT was used to visualize and quantify the degree of deformation and fluid distribution corresponding with each stress condition and injection cycle. Micro‐CT images were segmented using a gradient‐based method to identify fluids (e.g., oil and water), and solid phase redistribution throughout the different experimental stages. Changes in porosity, tortuosity, and specific surface area were quantified as a function of applied confining pressure. Results demonstrate varying degrees of sensitivity of these properties to confining pressure, which suggests that caution must be taken when considering scalability of these properties for practical modeling purposes. Changes in capillary number with confining pressure are attributed to the increase in pore velocity as a result of pore contraction. However, this increase in pore velocity was found to have a marginal impact on average phase trapping at different confining pressures.